ETUDE EPIDEMIOLOGIQUE DES CAS D’INTOXICATIONS AIGUES TRAITES A L’HOPITAL DE SETIF ENTRE JANVIER 2008 ET AVRIL 2012 (EST- ALGERIE) - Mahdeb, Nadia; Mariem, Sahnoune; Abdelouahab, Bouzidi (European Scientific Journal, ESJ, 2013)
A retrospective study of acute poisoning recorded in University Hospital Centre (CHU) of Setif (East-Algeria) between January 2008 and April 2012 was performed. It aimed to determine the number and types of poisoning streated their distribution according to sex and age of patients, and the type of toxic agents involved and intentionality. Data retrieval of records in the emergency department of the CHU of Setif revealed 4003 cases of acute poisoning, with an age ranging from 03 days to 86 years. The female patients predominated with 56.98%, a sex ratio of 1.33. The frequencies of the highest poisoning were recorded in urban areas with 80.29% against 19.71% in rural or peri-urban areas. Persons 16 to 25 years, and children aged 0 to 4 years are the most affected by poisoning, with respective shares of 31.77% and 21.17%. The nature of the poisoning is varied, and most products are initially incriminated drugs (39.34%), followed by CO and gas (31.77%) and pesticides (13.54%). To reduce the incidence of acute accidental and intentional poisonings, prevention and improvement of socio-economic conditions remain the treatment of choice.